Response to subsequent antiseizure medications after first antiseizure medication failure in newly diagnosed epilepsy - Hersi, Hire; Saarinen, Jukka T.; Raitanen, Jani; Peltola, Jukka (Frontiers in Neurology, 2022)
Objective There is a lack of studies using the International League Against Epilepsy (ILAE) recommendation to define drug-resistant epilepsy (DRE). This study evaluated the seizure freedom rates of substitution or add-on and subsequent antiseizure medication (ASM) therapies using different proposed definitions of DRE or ASM trials in patients with a failed first ASM. We also identified prognostic factors for 1-year seizure freedom. Methods This study included 459 patients with epilepsy of whom 151 were not seizure-free after the first ASM. Multilevel mixed-effects logistic regression was used to examine the correlation between observations from the same patient. Results The overall seizure freedom rate with the first and subsequent ASMs was 88.0% (404/459). The rate of DRE when defined as the failure of two ASMs for any reason was 20.0%, and according to the ILAE definition of DRE, it was 16.3%. After failing the first ASM, 63.6% of patients (96/151) became seizure free with subsequent ASMs and tried an average of 1.9 ASMs (range 1–5). Of the patients who achieved 1-year seizure freedom, 10.1% (41/404) were taking polytherapy and there was no difference between substitution and add-on. All the patients with generalized epilepsy were seizure-free. A favorable prognostic factor was age >60 years and an EEG without epileptiform activity. The efficacies of the different ASMs were largely similar, but drugs that enhanced GABA-mediated inhibitory neurotransmission had the lowest seizure freedom rate. Significance In adults with newly-diagnosed epilepsy, 1-year seizure freedom was achieved for almost 90% of the patients. After failing the first ASM, two-thirds of the patients responded to subsequent ASM regimens. Our results support the feasibility and applicability of the ILAE concept of an adequate ASM trial and the failure of two ASMs as a definition of DRE.